2017
DOI: 10.1016/j.jfluidstructs.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

An efficient fluid–structure interaction model for optimizing twistable flapping wings

Abstract: Spanwise twist can dominate the deformation of flapping wings and alters the aerodynamic performance and power efficiency of flapping wings by changing the local angle of attack. Traditional Fluid-Structure Interaction (FSI) models, based on Computational Structural Dynamics (CSD) and Computational Fluid Dynamics (CFD), have been used to investigate the influence of twist on the power efficiency. However, it is impractical to use them for twist optimization due to the high computational cost. On the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…From (17), it is clearly seen that it does not vary with the body mass. As is shown in (18), the lumped parameter is inversely proportional to the average lift coefficient, which indicates that the larger the lumped parameter is, the less lift is produced at a constant angle attack. Additionally, the larger the lumped parameter is, the shorter and rounded the wing is.…”
Section: Flapping Wing Lift Productionmentioning
confidence: 83%
See 2 more Smart Citations
“…From (17), it is clearly seen that it does not vary with the body mass. As is shown in (18), the lumped parameter is inversely proportional to the average lift coefficient, which indicates that the larger the lumped parameter is, the less lift is produced at a constant angle attack. Additionally, the larger the lumped parameter is, the shorter and rounded the wing is.…”
Section: Flapping Wing Lift Productionmentioning
confidence: 83%
“…In this study, the average value of various species is considered and studied. From (18), it can be observed that the aspect ratio and lumped parameter are in inverse proportion, which indicates that the species with high aspect ratio have a lower lumped parameter. The relationship of AR and lumped parameter k with body mass and wing length are plotted in Figures 6-8.…”
Section: Wing Loading Aspect Ratio and Lumped Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Based on known flapping kinematics and measured or estimated aerodynamic coefficients, thin airfoil theory is used to predict aerodynamic forces and moments acting on a single blade element, and these differential forces are integrated over the wing surface to estimate total aerodynamic forces. BET is often restricted to describing the aerodynamics of rigid wings, though Wang et al developed a fluid-structure interaction (FSI) model based on BET to estimate the aerodynamics of twistable wings [28]. Other researchers have used Theoderson's unsteady aerodynamic model to predict flapping forces of flapping wings [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…These equations can generally be discretized on a 2-or 3-D grid by the use of well-established techniques such as the Finite Volume (FV) or Finite Element (FE) methods. With the advent of new and more powerful hardware, including Central Processing Unit (CPU) and Graphics Processing Unit (GPU), the efficiency and effectiveness of the aforementioned methodologies have improved significantly, allowing the study of real-life problems [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%